PERBEDAAN TINGKAT EFEKTIVITAS ANTARA PENERAPAN MODEL INKUIRI DENGAN PENERAPAN COOPERATIVE LEARNING TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPA - Budiman, Ferri (2013)
This research stimulated by the low level of student learning outcomes in Science subjects at SDN 3 Cibodas where obtaining the average grade obtained was 61,30 or is below the value of KKM who applied by the school amounted to 62 as well as the students themselves value where more than 50% of students in grade 5 Science subjects values obtained under the KKM, for it researchers trying to test learning model which tried 2 models and Inquiry a model Cooperative Jigsaw type of restitution for applied in Science subjects and where a more effective learning model applied in Science subjects. The research was carried out using Descriptive Survey method and implemented at SDN 3 Cibodas subdistrict of West Bandung Regency Lembang. The subject of this research is the use of class 5B model Inquiry, amounting to 27 students and a class 5A, amounting to 33 students who use Jigsaw Cooperative Learning model type. The planning of learning that is conducted is the determination of the measures of the model Inquiry and models of Cooperative Learning, Jigsaw-type step model is a stage of Inquiry asked, investigation, produce, discuss, and reflect while the step type of Cooperative Learning model of Jigsaw is a stage reading, discussion, team reports, tests, and rekognisi. The activity of the teachers and students during the learning activity takes place quite well from both sides, the activity of students in grade Inquiry for learning 89,74 scored while the activity from the teacher during the lesson is get the percentage of 94,11%. Meanwhile, the activity of the students in the class of Cooperative Learning is a learning type of Jigsaw 88,33 during while the teacher activity during learning in Cooperative Learning class get a percentage of Jigsaw-type 94,44%. To determine the effectiveness of the results of the study used Ternormalisasi Gain formula advanced by Hake. Of research results obtained in a class that uses the model Inquiry obtained on average an increase of 0.49 learning outcomes. While in the class that uses this type of Cooperative Learning model Jigsaw obtained improved learning outcomes of 0.37. Key words: Inquiry, Cooperative Learning, learning outcomes, effectiveness Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa pada mata pelajaran IPA di SDN 3 Cibodas di mana perolehan rata-rata kelas yang didapat adalah 61,30 atau berada di bawah nilai KKM yang diterapkan oleh pihak sekolah sebesar 62 serta nilai siswa sendiri di mana lebih dari 50% siswa kelas 5 nilai mata pelajaran IPA yang diperoleh berada di bawah KKM, untuk itu peneliti mencoba menguji cobakan 2 model pembelajaran yaitu model Inkuiri dan model Cooperative lenting tipe Jigsaw untuk diterapkan di mata pelajaran IPA dan mana model pembelajaran yang lebih efektif diterapkan di mata pelajaran IPA. Penelitian ini dilaksanakan dengan menggunakan metode Survey Deskriptif dan dilaksanakan di SDN 3 Cibodas Kecamatan Lembang Kabupaten Bandung Barat. Yang menjadi subjek dari penelitian ini adalah kelas 5B yang menggunakan model Inkuiri yang berjumlah 27 siswa dan kelas 5A yang berjumlah 33 siswa yang menggunakan model Cooperative Learning tipe Jigsaw. Perencanaan pembelajaran yang dilakukan adalah penetapan langkah-langkah dari model Inkuiri dan model Cooperative Learning tipe Jigsaw, langkah dari model Inkuiri adalah tahap bertanya, investigasi, menghasilkan, berdiskusi dan refleksi sedangkan langkah dari model Cooperative Learning tipe Jigsaw adalah tahap membaca, diskusi, laporan tim, tes, dan rekognisi. Aktivitas guru dan aktivitas siswa selama pembelajaran berlangsung cukup baik dari kedua belah pihak, aktivitas siswa di kelas Inkuiri selama pembelajaran mendapat skor 89,74 sedangkan aktivitas dari guru selama pembelajaran adalah mendapatkan persentase 94,11 %. Sementara itu aktivitas siswa di kelas Cooperative Learning tipe Jigsaw selama pembelajaran adalah 88,33 sedangkan aktivitas guru selama pembelajaran di kelas Cooperative Learning tipe Jigsaw mendapatkan persentase sebesar 94,44%. Untuk mengetahui efektivitas dari hasil belajar digunakan rumus Gain Ternormalisasi yang dikemukakan oleh Hake. Dari hasil penelitian didapat bahwa di kelas yang menggunakan model Inkuiri diperoleh rata-rata peningkatan hasil belajar sebesar 0,49. Sedangkan di kelas yang menggunakan model Cooperative Learning tipe Jigsaw diperoleh peningkatan hasil belajar sebesar 0,37. Kata Kunci : Inkuiri, Cooperative Learning, hasil belajar, efektivitas